-2p+7=3x-(5p+1)

Simple and best practice solution for -2p+7=3x-(5p+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2p+7=3x-(5p+1) equation:


Simplifying
-2p + 7 = 3x + -1(5p + 1)

Reorder the terms:
7 + -2p = 3x + -1(5p + 1)

Reorder the terms:
7 + -2p = 3x + -1(1 + 5p)
7 + -2p = 3x + (1 * -1 + 5p * -1)
7 + -2p = 3x + (-1 + -5p)

Reorder the terms:
7 + -2p = -1 + -5p + 3x

Solving
7 + -2p = -1 + -5p + 3x

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '5p' to each side of the equation.
7 + -2p + 5p = -1 + -5p + 5p + 3x

Combine like terms: -2p + 5p = 3p
7 + 3p = -1 + -5p + 5p + 3x

Combine like terms: -5p + 5p = 0
7 + 3p = -1 + 0 + 3x
7 + 3p = -1 + 3x

Add '-7' to each side of the equation.
7 + -7 + 3p = -1 + -7 + 3x

Combine like terms: 7 + -7 = 0
0 + 3p = -1 + -7 + 3x
3p = -1 + -7 + 3x

Combine like terms: -1 + -7 = -8
3p = -8 + 3x

Divide each side by '3'.
p = -2.666666667 + x

Simplifying
p = -2.666666667 + x

See similar equations:

| 25=7m+4 | | -9+w=-32 | | 42.72=.99+27x | | -29-10n=-18n+91 | | 2=3(x-5)+1-2x | | 3b+17=29 | | 5(2x-7)+42-3x=2 | | 17k=5k-2 | | 10(-10)=0 | | 3x-x+10-12=-188 | | 42.72=.99+x | | 0.4(-0.04-7x)=-2.7x | | 12x-6x=36 | | 5z+2=17 | | -29-10n=-18n+9 | | a=x | | -4n+3=13 | | 14x+23=4x+173 | | 11-2x+8x+5=32 | | r+1/3=8/3 | | (x^2-2x)-180=0 | | 9=g+3 | | -(12-4x)+8(10-4x)= | | 34=t+15 | | x-5/3=10 | | 5(3x-4)+2=4(3x+2) | | 7+8x=98.2 | | -2/5y=-4/15 | | 15.99x-26.73=42.72 | | 0.05s+0.10(6000-s)=375 | | x+2=4(4x-6) | | 3x-5=1x-13 |

Equations solver categories